1992, A Year of Geography and History (Journal of Parents and Teachers, 2026)
Drawing on three of the thirteen modules from the MEC/89 Curriculum Framework, with regard to the Social Studies programme, this article proposes some key points for understanding the various topics, placing particular emphasis on the skills, values and attitudes that pupils are expected to acquire. In addition to presenting the topics within each module, it provides some methods for addressing them.
Keywords: Geography and History; MEC/89 Curriculum; Social Sciences